Psychometric properties of the Rosenberg self-esteem scale in Mexican university students - Valdés García, Karla Patricia; Reynoso-González, Oscar Ulises; Santana-Campas, Marco Antonio; De Luna-Velasco, Laura Elena; Hermosillo-De la Torre, Alicia Edith (Acta Universitaria, 2022)
This work aimed to evaluate the psychometric properties of the Rosenberg self-esteem scale in Mexican university students. The research was carried out under an instrumental design, with an incidental sample of 675 students from three institutions. From the literature review, three factorial configurations were evaluated: (1) univariate, (2) bifactorial, and (3) bifactorial with a general factor, with the maximum likelihood method. Results confirmed that the bifactorial model with a general factor presented the best psychometric properties (X2 [24] = 34.71; p = 0.073; CFI = 0.99; TLI = 0.99; RMSEA = 0.02 [0.00-0.04]; SRMR = 0.02; AIC = 96.71), together with adequate internal consistency values ​​(α = 0.87, 0.80, 0.79). Additionally, the authors presented a proposal for the scale and cut-off points to classify results. It is concluded that the Rosenberg self-esteem scale under a bifactorial model with a general factor presents appropriate psychometric properties for Mexican university students.